Breastfeeding in children with cleft lip and palate and its effect on surgical outcomes - Jar, Alabbas Abdulghani; Alotaibi, Adel Shabib; Alqahtani, Hussain Ali; Alshaqaqeq, Ghaida Ali; Alandanoosi, Hosam Ibraheem; Alsulami, Sultan Rubayan; Alosaimi, Latifa Abdulrahman; Alyahya, Awatef Sliman; Alsulami, Musab Abdullah; Almohammadi, Abdulrhman Awad; Aljaghthami, Saud Obaid (International Journal Of Community Medicine And Public Health, 2023)
Breastfeeding is a fundamental aspect of infant nutrition and development. However, children born with cleft lip and palate face unique challenges in breastfeeding due to structural anomalies in their facial and oral regions. This study explores the intricate landscape of CLP, covering its epidemiology, complex etiology involving genetic and environmental factors, and the specific challenges breastfeeding children with CLP and their mothers encounter. This review emphasizes the critical role of surgical interventions in CLP management, discussing the timing, techniques, and outcomes of these procedures. While surgical repair of CLP can enhance breastfeeding outcomes, it may also introduce temporary complications, including feeding difficulties, pain, and discomfort. Addressing these challenges requires a multidisciplinary approach involving healthcare professionals, specialized feeding equipment, emotional support, and targeted interventions. Moreover, the emotional well-being of mothers of infants with CLP is highlighted as an essential component of breastfeeding success. Maternal stress and emotional distress can hinder breastfeeding, emphasizing the importance of emotional support and counseling services. Successful breastfeeding in children with CLP is achievable with the right strategies and support systems, like comprehensive care, which acknowledges the complexity of CLP and emphasizes the need for a collaborative healthcare approach to ensure that children with CLP receive optimal nutrition and care during their critical early developmental stages.